EVALUASI KUALITAS MAJALAH DINDING BERBASIS KOMPUTER PADA MATA KULIAH PUBLIKASI MODE - Pertiwi, Mentari (2014)
Evaluate the quality of the wall magazine conducted for measure the capabilities and assess the quality of the resulting product to increase an interesting visualization. This research aims to obtain data on the quality evaluation result based assement wall magazine of theme, rubric, article content, can apply the element and principal of layout, and the ability to operate the software . In this research benefit to be expected to improve the quality of assessment in order to improve the quality and standar wall magazine for a better future. The method used is descriptive analytic with a total sample by collecting the data through article archive documentation based on the assignment of creating wall magazine which consisted of 30 documentation articles as the samples which are related to the Fashion Publication assignment for the students of Design Management, Fashion Education Major of UPI batch 2010 and 2011. According to the result of the study, it can be concluded that largely of the students can create an interesting layout for wall magazine based on the quality assessment that interprets the theme and rubric. Reviewed , based on the quality assessment of managing the text element, the study result showed that more than half of the students involved in this study can apply the Headline, subhead, initial caps, bodytext, byline dan wordart, on the layout .Reviewed , based on the quality assessment of managing the visual element, the study showed that more than half of the students involved in this study can apply the Artworks,ornament, background, dan line, Then based on the quality assessment of managing the invisible element, the study showed that a half of the students involved in this study can apply the margin, grid, dan column.Then based on the quality assessment of layout arrangment principal, the study showed that largely of the majority of the respondents have the capability of presenting the quality of sequence, emphasis, balance and unity application, Then the last one was based on the quality assessment to operate software, the study showed that largely of the respondents have the capability of operate software, over all these data are excellent qualifications. Key Words : evaluation quality, wall magazine computer based , fashion publication. Mengevaluasi kualitas majalah dinding dilakukan untuk mengukur kemampuan dan menilai kualitas produk yang dihasilkan agar dapat meningkatkan tampilan visual yang lebih baik. Penelitian ini bertujuan untuk memperoleh data mengenai hasil evaluasi majalah dinding berdasarkan penilaian terhadap tema, rubrik, konten artikel, penerapan elemen dan prinsip-prinsip layout, serta kemampuan mengaplikasikan software. Manfaat pada penelitian ini diharapkan dapat meningkatkan kualitas penilaian guna meningkatkan mutu dan standar tugas pembuatan majalah dinding agar lebih baik di masa mendatang. Metode yang digunakan yaitu metode deskriptif analitik dengan sampel total sebanyak 30 eksemplar tugas majalah dinding mahasiswa konsentrasi manajemen desain Program Studi Pendidikan Tata Busana angkatan tahun 2010 dan 2011. Temuan penelitian menunjukan bahwa sebagian besar responden mampu mengelola tema, dan rubrik pada majalah dinding, dari kualitas elemen teks lebih dari setengahnya responden dapat mengolah teks yaitu Headline, subhead, initial caps, bodytext, byline dan wordart, dari kualitas elemen visual lebih dari setengahnya responden dapat mengolah Artworks,ornament, background, dan garis, dari kualitas invisible element menunjukan bahwa setengahnya responden dapat mengolah margin, grid, dan kolom, dari kualitas mengintegrasikan prinsip penyusunan layout sebagian besar responden mampu menerapkan prinsip sequence, emphasis, balance, dan unity, dan dari mengaplikasikan software sebagian besar responden mampu mengoperasikan tool pada pembuatan layout, keseluruhan data tersebut berada pada kualifikasi sangat baik. Kata Kunci: Evaluasi kualitas, Majalah Dinding Berbasis Komputer, Publikasi Mode.